The Mechanical and Fracturing of Rockburst in Tunnel and Its Acoustic Emission Characteristics - Xiangxin Liu; Sibo Zhan; Yanbo Zhang; Xiaolei Wang; Zhengzhao Liang; Baozhu Tian (Shock and Vibration)
The phenomenon of acoustic emission (AE) is associated with rock failure and rock fracturing. In order to investigate the influence of tectonic stress on rockburst in tunnel, a biaxial loading experiment system was used in this study. The excavation operation is undertaken at the center of samples to monitor the tunnel forming process in situ, and the different horizontal stresses can be studied by using the AE monitoring technique. The dynamical fracturing process of the tunnel model was summarized, and the timing parameters of AE signals in rockburst stages were obtained. The curves of AE energy and cumulative AE energy with time show a “step-like” rising trend before the occurrence of rockburst. The evolution of macro- and mesocracks is captured, and the mechanical conditions for a “V-shaped” rockburst pit are derived. As the horizontal stress increases, the effect of excavation unloading becomes more pronounced, and the damage caused by the rockburst intensifies. In the early stage of rockburst evolution, the fracturing type follows a model of tensile-shear mix model. A positive relationship between the ratio of shear fracturing type and the horizontal stress can be noted when the rock is about to burst, and the high intensity and the high energy released of from the rock-fracturing event have become evident. Thus, the results indicate that one should focus on monitoring both sides of the surrounding rock of the tunnel so as to extract the characteristics of the process of tunnel in tunnel. The applications of biaxial loading system and during an excavation operation provide a useful tool to simulate the rock burst in tunnel at an engineering site.